Childhood Poverty and Young Adults’ Allostatic Load - Evans, Gary W.; Kim, Pilyoung (Psychological Science, 2012)
Childhood poverty is linked to a host of physical and psychological disorders during childhood and later in life. In the study reported here, we showed that the proportion of childhood spent in poverty from birth to age 9 was linked to elevated allostatic load, a marker of chronic physiological stress, in 17-year-olds. Furthermore, this prospective longitudinal relationship was mediated by cumulative risk exposure at age 13. The greater the duration of early life spent in poverty, the greater the exposure to cumulative risk. This, in turn, leads to elevated allostatic load. Multiple psychological, biological, and neurological pathways likely account for the social patterning of psychological and physical disease.